2019
DOI: 10.1021/acs.jpcc.9b07350
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt and Iron Ions in MgO Nanocrystals: Should They Stay or Should They Go

Abstract: Identification and manipulation of transition-metal ion impurities in oxide nanoparticles require an in-depth understanding of their stability, segregation behavior, and, at the same time, knowledge about their surface reactivity. Powders of magnesium oxide nanoparticles with admixtures of iron or cobalt ions, as two next neighbors in the periodic table, were synthesized in the gas phase via injection of metal−organic precursors into the magnesium combustion flame followed by temperature quenching of resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 76 publications
0
21
0
Order By: Relevance
“…The production of transition metal oxide doped MgO nanocubes in the gas phase utilizes the decomposition of cobaltocene inside the strongly exothermic Mg combustion flame (Figure 1 a). Such an approach provides high control over the integral concentration and homogeneous distribution of the admixed cobalt ions over the metal oxide nanoparticles [6] . A dedicated annealing protocol with vacuum annealing at base pressures as low as p (O 2 )<10 −6 mbar (Figure 1 b) was developed for nanoparticle purification, that is, for the generation of particles with surfaces that are exempt from synthesis related carbonaceous species, adsorbed water or hydroxyls as remnants.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The production of transition metal oxide doped MgO nanocubes in the gas phase utilizes the decomposition of cobaltocene inside the strongly exothermic Mg combustion flame (Figure 1 a). Such an approach provides high control over the integral concentration and homogeneous distribution of the admixed cobalt ions over the metal oxide nanoparticles [6] . A dedicated annealing protocol with vacuum annealing at base pressures as low as p (O 2 )<10 −6 mbar (Figure 1 b) was developed for nanoparticle purification, that is, for the generation of particles with surfaces that are exempt from synthesis related carbonaceous species, adsorbed water or hydroxyls as remnants.…”
Section: Resultsmentioning
confidence: 99%
“…Our results of a recent X‐ray spectroscopy study on these nanoparticle powders revealed that the Co 2+ ions in MgO remain within the highly symmetric octahedral environment and do not change their (+2) valence state and are perfectly in line with the here presented results. A high definition of the cubic particle habit with a high abundance of sharp edges and corners is retained after annealing at 1173 K. Thus, annealing in vacuum and oxygen‐rich environment does not affect the hierarchy of surface energies and Co‐doped MgO(100) surfaces remain significantly lower in energy as compared to all other crystal planes [6] …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations